2014
DOI: 10.1080/09593330.2014.941310
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of full-scale carbon contactors for siloxane removal from biogas using online Fourier transform infrared spectroscopy

Abstract: In this study, online Fourier transform infrared (FTIR) spectroscopy has been used to generate the first comprehensive characterization of full-scale carbon contactors for siloxane removal from biogas. Using FTIR, two clear operational regions within the exhaustion cycle were evidenced: an initial period of pseudo-steady state where the outlet siloxane concentration was consistently below the proposed siloxane limits; and a second period characterized by a progressive rise in outlet siloxane concentration duri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 18 publications
1
10
0
Order By: Relevance
“…Engine manufacturers claim higher siloxane limits in biogas than other ECS, but there is a wide range of limits depending on the manufacturer, ranging from 12 mg/m 3 (Jenbacher) to 28 mg/ m 3 (Caterpillar) or 30 mg/m 3 (Waukesha) [6,69,129].…”
Section: Internal Combustion Engines (Ice)mentioning
confidence: 97%
See 3 more Smart Citations
“…Engine manufacturers claim higher siloxane limits in biogas than other ECS, but there is a wide range of limits depending on the manufacturer, ranging from 12 mg/m 3 (Jenbacher) to 28 mg/ m 3 (Caterpillar) or 30 mg/m 3 (Waukesha) [6,69,129].…”
Section: Internal Combustion Engines (Ice)mentioning
confidence: 97%
“…For example, a relative humidity of 50-70% can reduce the siloxanes adsorption capacity a factor of 10 or greater [4,106], probably as a result of water adsorption and formation of hydrogen bonds with oxygen functional groups on the adsorbent material surface, which block the adsorption sites. Moreover, Hepburn et al [69] showed that bed dimensioning (height-diameter ratio) also plays an important role in the siloxane adsorption capacity, concluding that operation at high Reynolds number favoured siloxane adsorption.…”
Section: Adsorption Processesmentioning
confidence: 98%
See 2 more Smart Citations
“…) or of carbon bed breakthrough (Hepburn et al . ). In addition, there is a lag time between sampling and receiving the results (Hepburn et al .…”
Section: Introductionmentioning
confidence: 97%